2022
DOI: 10.1371/journal.pone.0276878
|View full text |Cite
|
Sign up to set email alerts
|

The effect of state and trait power on financial risk-taking: The mediating and moderating roles of optimism

Abstract: The research aimed to further develop knowledge on the mechanisms that enhance risk-taking propensities among powerful people. Three studies (N1 = 328, N2 = 388, N3 = 267) investigated the role of optimism in the relationship between sense of power and financial risk-taking, controlling for the state of power. Study 1, correlational, analyzed whether the relationship between sense of power and risky financial choices is serially mediated by general optimism and financial risk perception. The results confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…To achieve this, we test a model in which the state of focus on rewards versus threats and the state of power jointly moderate the link between sense of power and risk propensity. We expect a moderating role of state of power as previous studies have shown that the effects of sense of power and state of power are usually consistent, yet they might interact with each other (Rucker et al, 2012;Sek sci nska, Rudzinska-Wojciechowska, & Jaworska, 2022;Sek sci nska, Rudzinska-Wojciechowska, & Kusev, 2022).…”
Section: The Theoretical Background Of the Modelmentioning
confidence: 92%
See 4 more Smart Citations
“…To achieve this, we test a model in which the state of focus on rewards versus threats and the state of power jointly moderate the link between sense of power and risk propensity. We expect a moderating role of state of power as previous studies have shown that the effects of sense of power and state of power are usually consistent, yet they might interact with each other (Rucker et al, 2012;Sek sci nska, Rudzinska-Wojciechowska, & Jaworska, 2022;Sek sci nska, Rudzinska-Wojciechowska, & Kusev, 2022).…”
Section: The Theoretical Background Of the Modelmentioning
confidence: 92%
“…Moreover, the effects of state of power and sense of power are usually consistent (e.g., Anderson & Berdahl, 2002; Anderson & Galinsky, 2006; Cote et al, 2011; for a review, see Rucker et al, 2012). However, some studies have found an interaction effect between state of power and sense of power (Chen et al, 2009; Sekścińska & Rudzinska‐Wojciechowska, 2021; Sekścińska, Rudzinska‐Wojciechowska, & Jaworska, 2022; Strelan et al, 2014). For this reason, it is crucial to consider both components of power.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations